Experimental investigation of the hydro-elastic response of a spar-type floating offshore wind turbine. (1st July 2022) - Leroy, V.; Delacroix, S.; Merrien, A.; Bachynski-Polić, E.E.; Gilloteaux, J.-C.
Abstract: As the size of floating wind turbines continues to increase, floating platforms reach dimensions that make their elastic and hydro-elastic behaviour significant. Several works in connection with the numerical modelling of the elastic behaviour of these wind turbines have been carried out but few validation data are available. This study focuses on the hydro-elastic response of a large floating wind turbine, in regular waves and severe sea-states. A new experimental wind turbine model has been designed to represent a 1:40 Froude-scaled spar platform carrying the DTU 10 MW turbine. The main challenge is here to reproduce a 1st bending mode frequency and hydrodynamic loads representative of a realistic large floating wind turbine. The platform model is made of a flexible backbone, reproducing the correct flexibility, and light floaters fixed on it provide the correctly scaled geometry. This experimental model is tested in various conditions including regular waves of several periods and steepness, and irregular waves of various intensity, including extreme 50-year return period conditions. Highly nonlinear hydroelastic responses are observed in regular waves when higher order hydrodynamic loads excite the bending mode. In irregular sea-states, this behaviour was also triggered by strongly nonlinear effects resulting in a springing or ringing response of the system. This highlights the importance of nonlinear hydrodynamics in hydro-elastic analysis of large floating wind turbines. Eventually, the collected database could be relevant for a more advanced analysis with comparison to both linear and nonlinear hydro-elastic simulation tools. Graphical abstract: Highlights: Experimental modelling of a 10 MW spar–type FOWT, including flexibility of the platform. The first flexible bending mode frequency of the spar and tower is Froude scaled. Strongly nonlinear hydrodynamic loads triggered the resonance of the first bending mode. Ringing/springing response was observed and measured in steep irregular sea-states.